Automation, offshoring, and the role of public policies - Bernhard Schmidpeter; Rudolf Winter-Ebmer (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
We provide comprehensive evidence on the consequences of automation and offshoreability on the career of unemployed workers and the role of public policies. Using almost two decades of administrative data for Austria, we find that risk of automation is reducing the job finding probability; a problem which has increased over the past years. We show that this development is associated with increasing re-employment wages and job stability. Taken together, our findings imply a trade off between quantity and quality in these jobs. Provided training is beneficial in counteracting the negative impact of automation on the job finding rate but we find mixed effects in terms of post-unemployment wages. – – In diesem Papier evaluieren wir die Auswirkung von technologischem Fortschritt sowie Offshoring auf die Karriere von arbeitslosen Individuen. Wir evaluieren dabei auch explizit die Rolle von Weiterbildungsmaßnahmen. Unsere Ergebnisse zeigen, dass technologischer Fortschritt sich negativ auf die Einstellungswahrscheinlichkeiten auswirkt, ein Problem, das sich über die letzten Jahre verstärkt hat. Wir finden aber auch, dass wenn neue Arbeit gefunden wird, technologischer Fortschritt zu höheren Löhnen und stabileren Arbeitsverhältnissen führen kann. Weiterbildungsmaßnahmen während der Arbeitslosigkeit sind im Allgemeinen erfolgreiche Konzepte, um den negativen Auswirkungen des technologischen Fortschritts auf die Einstellungswahrscheinlichkeiten entgegenzuwirken. Wir finden hingegen gemischte Ergebnisse in Bezug auf Einstellungslöhne.
Keywords: J64; J68; J31; J24; 330; labor market polarization; technological change; offshoring; active labor market programs; unemployment